Distinct patterns of histone methylation and acetylation in human interphase nuclei - Skalníková, M; Bártová, E; Ulman, V; Matula, P; Svoboda, D; Harnicarová, A; Kozubek, M; Kozubek, S (Physiological research, 2007)
To study 3D nuclear distributions of epigenetic histone modifications such as H3(K9) acetylation, H3(K4) dimethylation, H3(K9) dimethylation, and H3(K27) trimethylation, and of histone methyltransferase Suv39H1, we used advanced image analysis methods, combined with Nipkow disk confocal microscopy. Total fluorescence intensity and distributions of fluorescently labelled proteins were analyzed in formaldehyde-fixed interphase nuclei. Our data showed reduced fluorescent signals of H3(K9) acetylation and H3(K4) dimethylation (di-me) at the nuclear periphery, while di-meH3(K9) was also abundant in chromatin regions closely associated with the nuclear envelope. Little overlapping (intermingling) was observed for di-meH3(K4) and H3(K27) trimethylation (tri-me), and for di-meH3(K9) and Suv39H1. The histone modifications studied were absent in the nucleolar compartment with the exception of H3(K9) dimethylation that was closely associated with perinucleolar regions which are formed by centromeres of acrocentric chromosomes. Using immunocytochemistry, no di-meH3(K4) but only dense di-meH3(K9) was found for the human acrocentric chromosomes 14 and 22. The active X chromosome was observed to be partially acetylated, while the inactive X was more condensed, located in a very peripheral part of the interphase nuclei, and lacked H3(K9) acetylation. Our results confirmed specific interphase patterns of histone modifications within the interphase nuclei as well as within their chromosome territories.
Keywords: histony; Chromosomes, Human, X; fibroblasty; Cell Nucleus; centromera; Fibroblasts; hybridizace in situ fluorescenční; Centromere; Methylation; metylace; Image Processing, Computer-Assisted; imunohistochemie; Chromosomes, Human, Pair 14; buněčné jádro; Chromosomes, Human, Pair 22; algoritmy; Interphase; lidské chromozomy X; interfáze; lidské chromozomy, pár 14; počítačové zpracování obrazu; lidé; Immunohistochemistry; Humans; Acetylation; Algorithms; acetylace; In Situ Hybridization, Fluorescence; Histones; lidské chromozomy, pár 22